Pengaruh Motivasi Kerja Dan Lingkungan Kerja Non Fisik Terhadap Kepuasan Kerja Guru PNS SMA Negeri 1 Cimahi - Agnes Wulan S.P; Dian Lestari (Yayasan Riset dan Pengembangan Intelektual, 2026)
Job dissatisfaction among teachers—reflected in rising absenteeism and a lack of appreciation for their performance—serves as the background of this study. An unharmonious work atmosphere and insufficient psychological support in the school environment are also suspected to influence teacher satisfaction. This study aims to examine the influence of work motivation and the non-physical work environment on job satisfaction at SMA Negeri 1 Cimahi. Using a quantitative approach and a descriptive-verificative method, data were analyzed through multiple linear regression with the assistance of SPSS version 25. The results show that both work motivation and the non-physical work environment have a positive and significant influence on job satisfaction, both partially and simultaneously. Among the two variables, the non-physical work environment has a more dominant effect. These findings highlight the importance of creating a supportive work environment and strengthening motivation strategies to enhance teacher satisfaction and performance.